Fibrocartilaginous embolism during swimming: A case report. Issue 5 (18th June 2020) - Tsunogae, Marie; Ueda, Masayuki
Abstract: A 70‐year‐old woman presented sudden back pain and right leg monoplegia just after her coach pushed her back during swimming. Magnetic resonance imaging revealed a thoracic spinal infarction, and computed tomography showed Schmorl's nodules and air densities in the intervertebral disks near the spinal lesion, indicating disk degeneration. A diagnosis of fibrocartilaginous embolism, caused by minor compression of intervertebral disks, was made. Physicians should consider fibrocartilaginous embolism as a cause of spinal infarction in patients without any risk of embolization, atherosclerosis, or surgical history.